ADL disability and death in dementia in a French population‐based cohort: New insights with an illness‐death model. Issue 8 (18th April 2016) - Delva, Fleur; Touraine, Celia; Joly, Pierre; Edjolo, Arlette; Amieva, Hélène; Berr, Claudine; Rouaud, Olivier; Helmer, Catherine; Pérès, Karine; Dartigues, Jean‐François
Abstract: Introduction: Transition to bathing or dressing disability is a milestone in the evolution of dementia. We examined the transition to disability in these specific activities and considered death to be a competitive event and age and sex to be prognostic factors. Methods: From a large cohort of 570 incident dementia cases screened in two prospective population‐based cohorts, the Paquid study, and the Three‐City study, we estimated the probabilities of remaining nondisabled, becoming disabled in bathing or dressing, or dying after the diagnosis using an illness‐death model. Results: On average, approximately half of the period (3 years) of living with dementia was free of disability. In women, a higher survival rate was associated with an average of 1 additional year with disability. Discussion: The joint prediction of death and disability in dementia by an illness‐death model gives original and useful parameters for the prognosis and management of dementia.